1980
DOI: 10.1016/0005-2736(80)90504-0
|View full text |Cite
|
Sign up to set email alerts
|

The action of cobra venom phospholipase A2 isoenzymes towards intact human erythrocytes

Abstract: Summary1. Cobra venom phospholipase A2 from three different sources has been fractionated into different isoenzymes by DEAE ion-exchange chromatography. 2. Treatment of intact human erythrocytes with the various isoenzymes revealed significant differences in the degree of phosphatidylcholine hydrolysis in those cells. 3. It is argued that the plateaus observed in dose-response curves for such treatments may be caused by an increase in lateral surface pressure within the outer half of the membrane due to the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

1981
1981
1993
1993

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…It has been suggested that this effect is a consequence of the production of the split products, lysolecithin and free fatty acids, which cause an increase in lateral surface pressure in the outer monolayer. This pressure may reach a certain level above which the enzyme can no longer penetrate (Roelofsen et al, 1980). In agreement with the above monolayer studies, it appears that porcine AMPA in contrast to [Lau-Lys116] porcine and [Pal-Lys10] bovine AMPAs is able to degrade the lecithin in the intact human red cell and, most interestingly, to do so at a much higher rate and with greater efficiency than Naja naja PLA (Figure 5).…”
Section: Discussionsupporting
confidence: 76%
“…It has been suggested that this effect is a consequence of the production of the split products, lysolecithin and free fatty acids, which cause an increase in lateral surface pressure in the outer monolayer. This pressure may reach a certain level above which the enzyme can no longer penetrate (Roelofsen et al, 1980). In agreement with the above monolayer studies, it appears that porcine AMPA in contrast to [Lau-Lys116] porcine and [Pal-Lys10] bovine AMPAs is able to degrade the lecithin in the intact human red cell and, most interestingly, to do so at a much higher rate and with greater efficiency than Naja naja PLA (Figure 5).…”
Section: Discussionsupporting
confidence: 76%
“…Phospholipases have been used extensively to determine membrane phospholipid organization in RBC from normal individuals (20)(21)(22)(23). Among these phospholipases are phospholipase A2 from bee venom and sphingomyelinase C from Staphylococcus aureus.…”
Section: Introductionmentioning
confidence: 99%
“…The failure of phospholipase A 2 (either from snake or bee venom) to degrade all of its substrates present in the outer membrane layer of an erythrocyte has been well documented for the human red cell [3,23]. It has been argued [37] that the action of the phospholipase A 2 ceases as a consequence of an increase in lateral surface pressure in the outer monolayer of the intact cell, which is caused by the generation of split products (lysophospholipids and free fatty acids) herein. Hydrolysis of sphingomyelin by sphingomyelinase C is believed to have the opposite effect, namely, a decrease in lateral surface pressure [3,37].…”
Section: Discussionmentioning
confidence: 99%
“…It has been argued [37] that the action of the phospholipase A 2 ceases as a consequence of an increase in lateral surface pressure in the outer monolayer of the intact cell, which is caused by the generation of split products (lysophospholipids and free fatty acids) herein. Hydrolysis of sphingomyelin by sphingomyelinase C is believed to have the opposite effect, namely, a decrease in lateral surface pressure [3,37]. Including this enzyme in incubations with phospholipase A 2, therefore, enables the latter phospholipase to degrade its substrates in the outer monolayer of intact human erythrocytes to completion [3,23].…”
Section: Discussionmentioning
confidence: 99%